REKONSTRUKSI POSTER SEBAGAI MEDIA ASPIRASI DAN PROPAGANDA MAHASISWA - Irfan Arifin; Nurjayanti Nurjayanti (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2024)
This article describes posters as an alternative medium for conveying messages and their relationship with social movements. This shows how posters should be represented as an appropriate medium for coveying aspirations and propaganda. This study shows that posters are used as a tool to express aspirations and propagate important ideas for students, and how posters are reconstructed as an effective medium for aspirations and propaganda for students. The research method used is literature study involving three main stages, identifying sources, collecting and analyzing data. Researches analyze how poster design can influence viewer acceleration and response through theories of information processing, perception and mass communication, so that visual communication strategies can be applied to achieve certain goals. The results of this research describe that in designing posters as an effective medium for conveying aspirations and propaganda, several factors must be considered, including creativity, effectiveness, conceptual design, media implementation, and recommendations for development and improvement which are expected to provide practical implications for visual communication designers and students in utilizing posters as a medium to convey aspirations and propaganda.